Clinical and Periprocedural Pain Management for Uterine Artery Embolization - Spencer, Elizabeth Brooke; Stratil, Peter; Mizones, Heidi (Seminars in Interventional Radiology, 2013)
Uterine artery embolization has Level A data supporting excellent safety and efficacy in treating symptomatic uterine leiomyomata. However, there is a perception that either postprocedural pain is severe or poorly managed by the physician performing these procedures. This has led some primary care physicians to omit this procedure from the patients' options or to steer patients away from this procedure. A few simple techniques (pruning of the vascular tree and embolizing to 5–10 beat stasis) and fastidious pre-, intra-, and post-procedural management can nearly eliminate significant pain associated with embolization. Specifically, early implementation of long-acting low-dose narcotics, antiemetics and anti-inflammatory medications is critical. Finally, the use of a superior hypogastric nerve block, which takes minutes to perform and carries a very low risk, significantly reduces pain and diminishes the need for narcotics; when this technique was used in a prospective study, all patients were able to be discharged the day of the procedure. In the authors' experience, patients treated in this manner largely recover completely within 5 days and have a far less traumatic experience than patients traditionally treated with only midazolam (Versed) and fentanyl citrate (fentanyl) intraprocedurally, and narcotics and nonsteroidal antiinflammatory drugs postprocedurally.
Keywords: uterine fibroid embolization; UAE; pain; superior hypogastric nerve block; postembolization syndrome; interventional radiology